2022
DOI: 10.1108/aea-08-2021-0199
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining teleworking before and during COVID-19: some evidence from Spain and Andalusia

Abstract: Purpose This study aims to analyse the inequalities in access to teleworking in Spain. More specifically, the study examines what factors determine remote working in a pre-pandemic period and during the state of alarm (March 2020). Moreover, the study examines whether telecommuting is related to the likelihood of suffering emotional disorders during lockdowns. Design/methodology/approach The methodological approach followed to analyse access to teleworking mainly consists of the estimation of ordered respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…These results show that telework can exert both positive and negative effects [17]. Additionally, other studies found no significant relationship between the place of work and emotional disorders [18]. These unclear findings direct scholars and practitioners towards other variables such as job teleworkability [19] and employees' preference for telework [20], in order to clarify how to ensure positive telework effects while preventing any negative impacts.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…These results show that telework can exert both positive and negative effects [17]. Additionally, other studies found no significant relationship between the place of work and emotional disorders [18]. These unclear findings direct scholars and practitioners towards other variables such as job teleworkability [19] and employees' preference for telework [20], in order to clarify how to ensure positive telework effects while preventing any negative impacts.…”
Section: Introductionmentioning
confidence: 76%
“…Due to the rapid growth of telework during the pandemic, a great deal of literature was produced on telework and well-being [4,9,10]. However, the obtained results showed dissimilar or even contradictory findings [13][14][15][16][17][18]. Thus, in order to contribute to clarifying how telework can positively impact on employees' well-being, three telework relevant characteristics were studied: teleworkability, preference for telework, and telework intensity.…”
Section: Discussionmentioning
confidence: 99%
“…On-site workers (11) faced challenges related to extended working hours and difficulty disconnecting from work. Similarly, teleworkers (35) and hybrid workers (9) struggled to disconnect digitally, experiencing extended working hours an issue supported by previous research (Caparr os Ruiz, 2022;Ngamkroeckjoti et al, 2022).…”
Section: Barriersmentioning
confidence: 82%
“…Going further, some researchers suggest that, in Spain, among other southern European countries, companies do not seriously consider the possibility of implementing work schedule arrangements for employees or employers ( Chung and Tijdens, 2012 ; Caparrós Ruiz, 2022 ). This factor seems plausible in the case of Spain and sheds some light on the way organizations manage telecommuting (outside of the COVID-19 outbreak) given that this modality can provide some flexibility and variety to employees.…”
Section: Telecommuting In Spain and Kazakhstanmentioning
confidence: 99%
“…Pastor et al argue that leading a workforce with high degrees of discretion involves adopting a congruent management philosophy that relies on results-oriented performance management systems. Another problem often named is the underdevelopment of skills needed to perform well remotely (Roca Pulido and Mart ınez-L opez, 2005;Caparr os Ruiz, 2022).…”
Section: Organizational Culture and Climate Researchmentioning
confidence: 99%